Поняття публічної безпеки як об'єкта адміністративно-правового регулювання - Герасимчук, Р. В.; Herasymchuk , R. V. (Європейські перспективи. - 2021. - № 3. - С. 198-203, 2021)
Запропоновано авторське визначення поняття публічної безпеки як об’єкта адміністративно-правового регулювання. Розкрито сутність та зміст понять «публічний», «безпека» та «публічна безпека». Узагальнено наукові думки з приводу тлумачення поняття «публічна безпека» в межах адміністративно-правової науки, зокрема, виділено особливості публічної безпеки як об’єкта адміністративно-правового регулювання.

The following conclusions have been formulated, which characterize the concept of public safety in general as an object of administrative and legal regulation, in particular: 1) in its form, public safety is a set of social relations, on which the action of the norms of the administrative branch of law is directed in order to regulate and organize them; 2) legal relations in the field of public security arise between the society of our country and the state (in the form of its authorized bodies and their officials); 3) the purpose of the activity of the state and other authorized entities that carry out activities in the direction of ensuring public safety is the formation of a safe environment on the territory of our state, which provides for the inviolability of the rights, freedoms and interests of people and citizens; 4) public safety is ensured with the help of a special legal toolkit, which may include measures of state coercion implemented in the interests of society in order to overcome destructive factors affecting it. It was found that public safety as an object of administrative and legal regulation should be characterized as a set of social and legal relations that arise between society and the state regarding the creation of a safe environment, as well as the protection of the rights and interests of every person and citizen in all spheres social life, which is carried out using special tools and means defined by the norms of administrative law, the use of which implies the possibility of using methods of state coercion.

Предложено авторское определение понятия публичной безопасности как объекта административно-правового регулирования. Раскрыты сущность и содержание понятий «публичный», «безопасность» и «публичная безопасность». Обобщены научные мнения по поводу толкования понятия «публичная безопасность» в пределах административно-правовой науки, в частности, выделены особенности публичной безопасности как объекта административно-правового регулирования.
Keywords: безпека; security; безопасность; публічна безпека; public safety; публичная безопасность; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование